Assessment of knowledge and attitude towards malaria transmission and prevention among school children in Rwanda - Marie Louise Umwangange; Geldine Chironda; Nkurunziza Aimable; Samuel Cumber; Madeleine Mukeshimana (Elsevier, 2023)
Background: Despite malaria being integrated into primary school education, the knowledge gap and negative attitude towards this topic still exists among school children. Aim: This study aimed at assessing knowledge and attitude towards malaria transmission and prevention among school children in Rwanda. Methods: A descriptive correlational study design was used. A random sample of 160 participants was selected. A validated structured interview schedule was used to collected data and face to face method was used. Data was analysed using descriptive and inferential statistics of the Pearson's correlation coefficient, and linear regression analysis. Results: Forty-five (28.13 %) had high knowledge, 108 (67.5 %) moderate and 7 (4.38 %) low knowledge on malaria transmission and prevention. Sixty-four (40 %) demonstrated positive attitude and 96(60 %) negative attitudes towards malaria prevention. A significant weak positive correlation between knowledge and attitude (r = 0.162, p = 0.041) was found. Linear regression analysis revealed knowledge to contributes only 2.6 % of increase in attitude (R2 = 0.026). Conclusion: Moderate levels of malaria knowledge coupled with negative attitudes among school children towards malaria transmission and prevention were identified. Health professionals should devise health education program during community outreach to intensify individualized strategies that will improve knowledge and attitudes of school children in Rwanda.